Literature review on green logistics - Ναρλιάν, Αλέξανδρος (2020)
The effect of logistics on the climate change and on environmental pollution, has caused recently growing attention of the industry sector, so as to renovate their supply chain in more environmentally friendly ways. Green operations in freight transport, storage and packaging and green IT systems have become extensive and significant, connecting the effective and efficient activity of business, with practices that have the least possible negative environmental consequences. This study highlights the knowledge about how logistics enterprises handle the challenge to start their green operations. It shows the connection between economy, environment and society within green logistics to achieve a sustainable target. The focus of this research is on the scheduling of the production and the distribution network under green logistics aspects. It addresses the influence of environmental impacts to the supply chain, taking into consideration the complexity and dynamics of a logistics system and furthermore it analyzes economic and social prospects that occur from green logistics’ operations. In addition, this article is recommended to researchers and academics who intent to start their research in GL area, since its bibliometric results, created a profile for that area of knowledge, assisting in the identification of future researches and opportunities for researchers to apply their theories.